LEAFJAREA DURATION AND PHOTOSYNTHETIC YIELD IN EARLYJMATURING TOMATO VARIETIES - P. M. Ahmedova (Овощи России, 2015)
The leaf-area duration and photosynthetic yield in early-maturing tomato varieties were studied in terms of planting system and degree of density of plants.